1999
DOI: 10.1007/bf01453442
|View full text |Cite
|
Sign up to set email alerts
|

Yeast and vertebrate nuclear-pore complexes: evolutionary conserved, yet divergent macromolecular assemblies

Abstract: The nuclear-pore complex (NPC), which consists of ca. 50 proteins called nucleoporins, is a huge macromolecular structure that spans the nuclear envelope and is an obligatory passage for molecules in transit between the cytoplasm and the nucleus. In the last years, major progress has allowed the characterization of the socalled "soluble phase" of nucleocytoplasmic transport, that involves transport substrates, import and export receptors of which some belong to the karyopherin-[~ family, and the small GTPase R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…From a central spoke ring embedded in the nuclear membranes emanate eight cytoplasmic and nuclear filaments, the latter joined by a distal ring to form the nuclear basket. A wealth of biochemical and genetic data on the protein subunits (nucleoporins) of NPCs has become available recently (Belgareh and Doye, 1999;Ryan and Wente, 2000), producing a basically complete inventory of yeast (Rout et al, 2000) and a steadily growing list of vertebrate nucleoporins.…”
Section: Introductionmentioning
confidence: 99%
“…From a central spoke ring embedded in the nuclear membranes emanate eight cytoplasmic and nuclear filaments, the latter joined by a distal ring to form the nuclear basket. A wealth of biochemical and genetic data on the protein subunits (nucleoporins) of NPCs has become available recently (Belgareh and Doye, 1999;Ryan and Wente, 2000), producing a basically complete inventory of yeast (Rout et al, 2000) and a steadily growing list of vertebrate nucleoporins.…”
Section: Introductionmentioning
confidence: 99%
“…Although the cytoplasmic filaments spread outward, the nuclear filaments conjoin distally to form a basket-like structure (8,9). This general architecture of NPCs is highly conserved between all eukaryotes, and many of the Nups are conserved across phyla (10). Genome analysis had revealed that half of the yeast nucleoporins contain phenylalanine-glycine (FG) repeats, either as FG, PSFG, FXFG, or GLFG repeats.…”
mentioning
confidence: 99%